A hard carbon material and its preparation method and application

By pre-oxidizing and carbonizing the mixture doped with asphalt and phosphorus and nitrogen, porous nitrogen-phosphorus co-doped hard carbon materials were prepared, which solved the problem of the lack of significant increase in sodium storage capacity and the reduction of first effect in the prior art. The problem of the problem is to achieve high capacity and high first-term efficiency electrochemical performance.

CN116835567BActive Publication Date: 2025-02-18SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310888640.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-02-18
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the first effect while increasing the sodium storage capacity of hard carbon materials of sodium ion batteries, and the process is complex and the cost is high.

Method used

By pre-oxidizing the mixture of asphalt and phosphorus and nitrogen as doping sources, porous nitrogen-phosphorus co-doped hard carbon material is formed, and the mesoporous structure and closed-porous structure are used to improve the sodium storage active site and carbon layer spacing. .

Benefits of technology

Without reducing the first effect, the reversible capacity of the sodium ion battery is significantly improved, and the material exhibits good electrochemical performance. The reversible capacity at a current density of 0.1C can reach 330mAh/g, and the first effect can reach more than 92%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116835567B_ABST
    Figure CN116835567B_ABST
Patent Text Reader

Abstract

The present invention discloses a hard carbon material and a preparation method and application thereof. The preparation method comprises the following steps: mixing asphalt and a doping source and then performing a pre-oxidation treatment to obtain a precursor; carbonizing the precursor at high temperature to obtain the hard carbon material; wherein the doping source comprises phosphorus and nitrogen, the softening point of the asphalt is lower than the decomposition temperature of the doping source, and the pre-oxidation temperature is greater than the softening point of the asphalt and less than the decomposition temperature of the doping source. The method of the present invention can improve the reversible capacity of a sodium ion battery without reducing the first effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy and relates to a hard carbon material and a preparation method and application thereof. Background Art

[0002] Environmental and energy crises have forced humans to urgently seek a new energy storage method that is clean, environmentally friendly and sustainable. Lithium-ion batteries, as a clean, recyclable energy storage device, have been widely used in production and life. However, due to the scarcity and uneven distribution of lithium resources, the price of lithium has been rising, which cannot meet the low-cost demand for large-scale energy storage.

[0003] Sodium-ion batteries have become a favorable competitor to lithium-ion batteries in large-scale energy storage due to their abundant sodium resources and low extraction and processing costs. Both sodium-ion batteries and lithium-ion batteries realize the charging and discharging process through the extraction / embedding of ions, but Na + The atomic radius is larger than that of Li + This leads to slow diffusion of sodium-ion batteries during the charge and discharge process and severe expansion of the negative electrode material, thus affecting the electrochemical properties of the material.

[0004] As the negative electrode material of sodium ion batteries, hard carbon has the advantages of large carbon layer spacing, high sodium storage capacity, low cost and environmental friendliness, so it has attracted extensive attention from researchers. At present, the precursors of hard carbon mainly include biomass, asphalt and resin. Among them, asphalt is expected to become a negative electrode material for industrial applications because of its controllable raw materials, low price and easy availability.

[0005] However, the carbon layer structure of asphalt materials tends to be ordered during the carbonization process, and there are fewer surface defects and functional groups, and fewer active sites for sodium storage, resulting in asphalt-based carbon materials having a lower sodium storage capacity as sodium ion negative electrodes. Currently, methods such as cross-linking, oxidation, and pore creation are commonly used to increase the capacity of materials.

[0006] For example, patent CN115259134A discloses a method for preparing hard carbon negative electrode materials by asphalt-based oxidation. The sodium storage performance of the material is improved by pore formation. The organic polymer and powdered asphalt are melted and blended, low-temperature pre-oxidized in an air atmosphere, and high-temperature carbonized in an inert atmosphere to finally form a hard carbon negative electrode material. This method improves the sodium storage capacity of the material to a certain extent. This method forms nanopores. More pores are likely to result in lower initial efficiency, and less pores will not significantly improve the capacity. Therefore, this method has limited room for improving capacity.

[0007] For example, CN115991467A discloses an oxidized asphalt-based hard carbon negative electrode material for sodium ion batteries, and its preparation method includes: crushing asphalt to obtain crushed asphalt; using a fluidized bed to adjust the temperature to oxidize the crushed asphalt to obtain an oxidized precursor; the oxidized precursor is sieved and then subjected to high-temperature carbonization treatment to prepare an oxidized asphalt-based hard carbon negative electrode material for sodium ion batteries. This method uses a fluidized bed to oxidize and modify the asphalt, so that the asphalt is uniformly oxidized, the degree of oxidation is deepened, the cross-linking structure is sufficient, the interlayer spacing after carbonization is larger, the closed pores are increased, and it is more conducive to sodium storage, and the yield of fully oxidized asphalt-based hard carbon is increased, and the cost is lower.

[0008] Another example is CN115676804A, which discloses a porous hard carbon negative electrode material based on asphalt, which first modifies the asphalt powder with a crosslinking agent or a modifier to improve the degree of disorder in the carbonization process, and then achieves uniform distribution of nano-asphalt particles and modifiers through spray drying and secondary granulation, improves the disordered state of asphalt in the sintering process, and at the same time, the uniform pore-forming agent inside the ball-forming process forms a multi-level pore structure during the acidification and washing process; finally, after high-temperature pre-oxidation, carbonization is combined with strong acid oxidation of the microcrystalline interface to enhance the repulsion between microcrystals, thereby achieving the purpose of increasing the interlayer spacing of hard carbon microcrystals. The prepared porous hard carbon negative electrode material has a large interlayer spacing of microcrystals and a multi-level pore structure, including mesopores and macropores, which effectively improves the sodium storage performance of the hard carbon material.

[0009] However, the above method only adjusts the structure and morphology of the carbon material by cross-linking, and the improvement of the capacity and initial efficiency is not obvious. It is necessary to develop a method to effectively increase the capacity of the material without losing the initial efficiency. Summary of the invention

[0010] In view of the above problems existing in the prior art, the object of the present invention is to provide a hard carbon material and a preparation method and application thereof. The method of the present invention can improve the reversible capacity of the sodium ion battery without reducing the initial efficiency.

[0011] In a first aspect, the present invention provides a method for preparing a hard carbon material, the preparation method comprising the following steps:

[0012] The asphalt and the doping source are mixed and then pre-oxidized to obtain a precursor;

[0013] Carbonizing the precursor at high temperature to obtain the hard carbon material;

[0014] Wherein, the doping source includes phosphorus and nitrogen, the softening point of the asphalt is lower than the decomposition temperature of the doping source, and the pre-oxidation temperature is greater than the softening point of the asphalt and less than the decomposition temperature of the doping source.

[0015] The method of the present invention pre-mixes the asphalt and the doping source and performs a pre-oxidation treatment. At this stage, the asphalt softens and presents a liquid-like state. At this time, the softened asphalt can wrap the doping source. As the pre-oxidation temperature increases, the asphalt wrapped with the doping source gradually begins to solidify. In the subsequent carbonization process, when the temperature is higher than the decomposition temperature of the doping source, the doping source decomposes to produce a phosphorus source and a nitrogen source (such as phosphate and ammonium salt), and some products are released in the form of gas to form mesopores. At the same time, the phosphorus source and the nitrogen source react with the carbon, and the phosphorus atoms and nitrogen atoms replace the carbon atoms on the six-membered ring or the five-membered ring, increasing the sodium storage active sites of the material. This sodium storage is mainly adsorption, which is conducive to the rapid release and embedding of sodium ions, thereby improving the dynamics of the material; in addition, after doping with phosphorus atoms and nitrogen atoms, the carbon layer arrangement changes from an ordered structure to a short-range ordered and long-range disordered structure, and the mutual accumulation of this structure forms a closed pore, and the sodium stored in this closed pore structure is reversible. Moreover, due to the large atomic radius of nitrogen atoms and phosphorus atoms, the spacing of the carbon layer is improved. The combined effect of the above factors effectively increases the capacity of the material without sacrificing initial efficiency.

[0016] The present invention prepares porous nitrogen-phosphorus co-doped hard carbon material through a simple one-step carbonization method, which has simple process, convenient operation and low cost, and is expected to be applied in industrial production.

[0017] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0018] Preferably, the softening point of the asphalt is 80°C-120°C, for example, 80°C, 90°C, 100°C, 105°C, 110°C, 115°C or 120°C, etc.

[0019] Preferably, the doping source is an ammonium phosphate salt, preferably ammonium polyphosphate.

[0020] Compared with monoammonium phosphate, the present invention uses ammonium polyphosphate, which is safer because monoammonium phosphate decomposes to generate metaphosphoric acid, which is highly toxic, while ammonium polyphosphate decomposes to generate phosphoric acid, which is non-toxic.

[0021] Preferably, the mass ratio of the asphalt to the doping source is 0.5-5, for example, 0.5, 0.6, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5, etc.

[0022] By changing the amount of doping source added, the doping amount of nitrogen atoms and phosphorus atoms, as well as the number and size of pores can be regulated. Within this preferred range, a rich mesoporous structure can be formed, the material has a high degree of disorder, and the number of closed pores is large. If the amount of doping source used is too high, a macroporous structure will be formed. This macroporous structure is a closed pore. The sodium storage sites provided by this structure are irreversible, which will reduce the primary effect of the material; if the amount of doping source used is too low, the doping amount of heteroatoms will be low, which is not conducive to the improvement of capacity.

[0023] As a preferred embodiment of the preparation method of the present invention, the mixing method is ball milling.

[0024] Preferably, the ball-to-material ratio of the ball mill is 20:1-5:1, for example, 20:1, 18:1, 15:1, 12:1, 10:1, 8:1 or 5:1.

[0025] Preferably, the ball milling time is 5 min-15 min, for example, 5 min, 6 min, 8 min, 10 min, 12 min, 13 min or 15 min.

[0026] Preferably, the pre-oxidation heating rate is 1°C / min-5°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, etc. If the heating rate is too low, the production efficiency will be affected; if the heating rate is too high, the oxidation will be insufficient and the cross-linking reaction cannot be carried out well.

[0027] Preferably, the pre-oxidation temperature is 180°C-300°C, for example, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C or 300°C.

[0028] Preferably, the pre-oxidation atmosphere is an oxygen atmosphere.

[0029] Preferably, the pre-oxidation time is 5h-15h, for example 5h, 6h, 7h, 8h, 10h, 11h, 13h, 14h or 15h, etc. If the pre-oxidation time is too short, it will lead to insufficient reaction; if the pre-oxidation time is too long, the material has undergone sufficient oxidation reaction, and the material performance is not greatly improved.

[0030] Preferably, the heating rate of the high temperature carbonization is 10°C / min-20°C / min, for example, 10°C / min, 12°C / min, 13°C / min, 15°C / min, 17°C / min, 18°C / min or 20°C / min.

[0031] Preferably, the temperature of the high temperature carbonization is 1300°C-1700°C, for example, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C or 1700°C.

[0032] Preferably, the high-temperature carbonization is carried out in an inert atmosphere.

[0033] The present invention does not limit the gas in the inert atmosphere, including but not limited to one gas or a combination of several gases selected from nitrogen, helium, neon or argon.

[0034] Preferably, the high temperature carbonization time is 2 h-4 h, for example, 2 h, 2.2 h, 2.5 h, 2.7 h, 2.8 h, 3 h, 3.5 h or 4 h.

[0035] As a preferred embodiment of the preparation method of the present invention, the preparation method comprises the following steps:

[0036] (1) Weighing a certain amount of asphalt and ammonium phosphate in proportion, and ball milling to obtain a mixture;

[0037] (2) placing the mixture in an oxygen atmosphere for pre-oxidation to obtain a pre-oxidation product;

[0038] (3) Carbonizing the pre-oxidized product at high temperature and cooling it to obtain a hard carbon material.

[0039] Among them, the mass ratio of asphalt to ammonium phosphate is 0.5-5, the softening temperature of asphalt is lower than the decomposition temperature of ammonium phosphate, the pre-oxidation heating rate is 1°C / min-5°C / min, the pre-oxidation temperature is 180°C-300°C, the pre-oxidation time is 5h-15h, the high-temperature carbonization is carried out in an inert atmosphere, the high-temperature carbonization heating rate is 10°C / min-20°C / min, the high-temperature carbonization temperature is 1300°C-1700°C, and the high-temperature carbonization time is 2h-4h.

[0040] In a second aspect, the present invention provides a hard carbon material prepared by the preparation method as described in the first aspect, wherein the hard carbon material is doped with nitrogen atoms and phosphorus atoms, and the hard carbon material contains closed pores.

[0041] The closed pores in the present invention are generally formed by carbon layer structural defects or carbon layer accumulation, and are generally smaller than 2 nm in size.

[0042] In a third aspect, the present invention provides a negative electrode, wherein the negative electrode comprises the hard carbon material as described in the second aspect as a negative electrode material.

[0043] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode as described in the third aspect.

[0044] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The method of the present invention pre-mixes the asphalt and the doping source and performs a pre-oxidation treatment. At this stage, the asphalt will soften and present a liquid-like state. At this time, the softened asphalt can wrap the doping source. As the pre-oxidation temperature increases, the asphalt wrapped around the doping source gradually begins to solidify. In the subsequent carbonization process, the purpose of doping and pore formation is achieved. The formed pores are mainly mesopores, and a large number of them are in a closed-pore state. The carbon layer presents a short-range ordered and long-range disordered structure, the sodium storage active sites are increased, and the distance between carbon layers is increased. The combined effect of the above factors effectively improves the capacity of the material without losing the first effect. The prepared hard carbon material exhibits good electrochemical properties. At a current density of 0.1C, the reversible capacity can be as high as 330mAh / g, and the first effect can be as high as 92% or more.

[0047] (2) The preparation method provided by the present invention has a simple process, is easy to operate, and has low cost, and is expected to be applied in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 is a SEM image of the hard carbon material obtained in Example 1.

[0049] Figure 2 This is the first charge and discharge curve of the hard carbon material obtained in Example 1. DETAILED DESCRIPTION

[0050] In order for those skilled in the art to better understand the present invention, the present invention will be further described in detail with reference to the following examples. It should be noted that the following examples do not constitute a limitation of the present invention.

[0051] Example 1

[0052] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0053] (1) 10 g of ammonium polyphosphate and 20 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0054] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 3°C / min, in an oxygen atmosphere, for 8 hours, for pre-oxidation treatment;

[0055] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0056] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0057] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 2.

[0058] Figure 1 This is a SEM image of the hard carbon material obtained in Example 1. It can be seen from the image that the particles are relatively round in shape and present a lamellar structure, which may be the result of ammonia etching produced by the decomposition of ammonium polyphosphate.

[0059] Example 2

[0060] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0061] (1) 10 g of ammonium polyphosphate and 5 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0062] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 3°C / min, in an oxygen atmosphere, for 8 hours, for pre-oxidation treatment;

[0063] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0064] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0065] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 0.5.

[0066] Example 3

[0067] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0068] (1) 10 g of ammonium polyphosphate and 30 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0069] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 3°C / min, in an oxygen atmosphere, for 8 hours, for pre-oxidation treatment;

[0070] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0071] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0072] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 3.

[0073] Example 4

[0074] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0075] (1) 10 g of ammonium polyphosphate and 50 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0076] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 3°C / min, in an oxygen atmosphere, for 8 hours, for pre-oxidation treatment;

[0077] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0078] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0079] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 5.

[0080] Example 5

[0081] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0082] (1) 10 g of ammonium polyphosphate and 20 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0083] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 1°C / min, in an oxygen atmosphere, for 8 hours, for pre-oxidation treatment;

[0084] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0085] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0086] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 2.

[0087] Example 6

[0088] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0089] (1) 10 g of ammonium polyphosphate and 20 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0090] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 5°C / min, in an oxygen atmosphere, for 8 hours, for pre-oxidation treatment;

[0091] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0092] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0093] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 2.

[0094] Example 7

[0095] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0096] (1) 10 g of ammonium polyphosphate and 20 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0097] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 3°C / min, in an oxygen atmosphere, for 5 h, for pre-oxidation treatment;

[0098] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0099] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0100] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 2.

[0101] Example 8

[0102] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0103] (1) 10 g of ammonium polyphosphate and 20 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0104] (2) placing the mixture in a tube furnace, heating it to 180°C at a rate of 3°C / min, in an oxygen atmosphere, for 12 h, for pre-oxidation treatment;

[0105] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0106] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0107] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 2.

[0108] Example 9

[0109] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0110] (1) 10 g of ammonium polyphosphate and 20 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 10:1, and the ball-milling time was 10 min to obtain a mixture;

[0111] (2) placing the mixture in a tube furnace, heating the temperature to 180°C at a rate of 3°C / min, in an oxygen atmosphere, for 15 h, for pre-oxidation treatment;

[0112] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0113] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0114] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 2.

[0115] Example 10

[0116] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0117] (1) 10 g of ammonium polyphosphate and 40 g of asphalt powder were ball-milled, the softening point of the asphalt was 80° C., the ball-milling ratio was 15:1, and the ball-milling time was 20 min to obtain a mixture;

[0118] (2) placing the mixture in a tube furnace, heating the temperature to 240°C at a rate of 2°C / min, in an oxygen atmosphere, for 10 h, for pre-oxidation treatment;

[0119] (3) After the pre-oxidation treatment, the oxygen was replaced by He, the temperature was raised to 1600°C at a heating rate of 15°C / min, and the heating time was 2h for high-temperature carbonization treatment;

[0120] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0121] In step (1) of this embodiment, the mass ratio of asphalt to ammonium polyphosphate is 4.

[0122] Embodiment 11

[0123] The difference from Example 1 is that the amount of ammonium polyphosphate in step (1) is adjusted so that the mass ratio of asphalt to ammonium polyphosphate is 0.3.

[0124] Example 12

[0125] The difference from Example 1 is that the amount of ammonium polyphosphate in step (1) is adjusted so that the mass ratio of asphalt to ammonium polyphosphate is 6.

[0126] Comparative Example 1

[0127] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:

[0128] (1) 30 g of asphalt powder was ball-milled, the softening point of asphalt was 80 °C, the ball-milling ratio was 10:1, and the ball-milling time was 10 min;

[0129] (2) The ball-milled powder was placed in a tube furnace and heated to 180°C at a heating rate of 3°C / min in an oxygen atmosphere for 8 h for pre-oxidation treatment;

[0130] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0131] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0132] Comparative Example 2

[0133] The difference from Example 1 is that the order of adding ammonium polyphosphate is different, specifically:

[0134] (1) 20 g of asphalt powder was ball-milled, the softening point of the asphalt was 80°C, the ball-milling ratio was 10:1, and the ball-milling time was 10 min. The ball-milled asphalt was placed in a tubular furnace, the heating rate was 3°C / min, the temperature was raised to 180°C, the atmosphere was oxygen, the heating time was 8 h, and pre-oxidation treatment was performed;

[0135] (2) mixing the product after the pre-oxidation treatment with 10 g of ammonium polyphosphate, and the resulting mixture is used in step (3);

[0136] (3) After the pre-oxidation treatment, the oxygen was replaced by Ar, the temperature was raised to 1500°C at a heating rate of 10°C / min, and the heating time was 3h for high-temperature carbonization treatment;

[0137] (4) After the high-temperature carbonization treatment is completed, the carbon material is cooled to room temperature to obtain a hard carbon material.

[0138] test:

[0139] The hard carbon materials of each embodiment and comparative example were used as negative electrode active materials to prepare negative electrodes, sodium sheets were used as counter electrodes, and 1.0 mol / L NaFPO 6 A mixed organic solution (the solvent is EC and DEC in a volume ratio of 1:1) was used as the electrolyte and a glass fiber membrane was used as the separator to prepare a CR2032 button cell. The electrochemical performance test was carried out at a current density of 0.1C, and the reversible capacity and first efficiency were recorded. The results are shown in Table 1.

[0140] Figure 2 This is the first charge and discharge curve of the hard carbon material obtained in Example 1. The capacity in the slope region (>0.1V) is mainly contributed by defect sites, and the capacity in the platform region (<0.1V) is mainly contributed by intercalation and closed pores.

[0141] Table 1

[0142] Example / Comparative Example Reversible capacity (mAh / g) First effect (%) Example 1 350 94.53 Example 2 355 92.01 Example 3 359 93.36 Example 4 330 94.93 Example 5 358 94.02 Example 6 340 94.60 Example 7 345 94.21 Example 8 352 94.50 Example 9 351 94.62 Example 10 348 94.57 Embodiment 11 349 89.35 Example 12 319 95.01 Comparative Example 1 280 89.23 Comparative Example 2 315 94.2%

[0143] analyze:

[0144] By comparing Example 1 with Examples 11-12, it can be seen that when the proportion of ammonium polyphosphate is high, the content of heteroatoms introduced is also high, and the specific capacity of the material is high. At the same time, due to the excessive addition of ammonium polyphosphate, the amount of gas generated by decomposition also increases, and the number of pore structures of the material also increases. Since part of the capacity of this open-pore structure is irreversible, the initial efficiency of the material is low. On the contrary, when the proportion of ammonium polyphosphate is low, the amount of heteroatoms introduced is also low, and the gas generated by decomposition is also less, so the material exhibits a higher initial efficiency and a lower capacity.

[0145] By comparing Example 1 with Comparative Example 1, it can be seen that the addition of ammonium polyphosphate introduces heteroatoms. At the same time, the gas produced by decomposition produces a pore structure during the escape process. Both of these factors lead to the material showing a higher capacity. At the same time, the introduction of nitrogen and phosphorus heteroatoms increases the disorder of the material, which is conducive to the formation of closed pores, increases the reversible capacity of the material, and thus improves the initial effect of the material.

[0146] By comparing Example 1 with Comparative Example 2, it can be seen that after the pre-oxidation, the asphalt is heated again and it is difficult to show a fluid state. Therefore, it is difficult to coat the ammonium polyphosphate when mixed with the ammonium polyphosphate. In the high-temperature carbonization stage, the released gas cannot form pores in the material. At the same time, the reaction activity of the asphalt after oxidation is reduced and it cannot fully react with the ammonium polyphosphate. Therefore, the capacity and the initial effect are reduced.

[0147] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a hard carbon material, characterized in that: The preparation method comprises the following steps: The asphalt and the doping source are mixed and then pre-oxidized to obtain a precursor; Carbonizing the precursor at high temperature to obtain the hard carbon material; Wherein, the mass ratio of the asphalt to the doping source is 0.5-5, the doping source is ammonium polyphosphate, the softening point of the asphalt is lower than the decomposition temperature of the doping source, and the pre-oxidation temperature is greater than the softening point of the asphalt and less than the decomposition temperature of the doping source; The pre-oxidation temperature is 180°C-300°C; The temperature of the high temperature carbonization is 1300°C-1700°C.

2. The preparation method according to claim 1, characterized in that: The softening point of the asphalt is 80°C-120°C.

3. The preparation method according to claim 1, characterized in that: The mixing method is ball milling.

4. The preparation method according to claim 3, characterized in that: The ball-to-material ratio of the ball mill is 20:1-5:

1.

5. The preparation method according to claim 3, characterized in that: The ball milling time is 5-15 min.

6. The preparation method according to claim 1, characterized in that: The heating rate of the pre-oxidation is 1°C / min-5°C / min.

7. The preparation method according to claim 1, characterized in that: The pre-oxidation atmosphere is an oxygen atmosphere.

8. The preparation method according to claim 1, characterized in that: The pre-oxidation time is 5h-15h.

9. The preparation method according to claim 1, characterized in that: The heating rate of the high temperature carbonization is 10°C / min-20°C / min.

10. The preparation method according to claim 1, characterized in that: The high-temperature carbonization is carried out in an inert atmosphere.

11. The preparation method according to claim 1, characterized in that: The high temperature carbonization time is 2h-4h.

12. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Weighing a certain amount of asphalt and ammonium phosphate in proportion, and ball milling to obtain a mixture; (2) placing the mixture in an oxygen atmosphere for pre-oxidation to obtain a pre-oxidation product; (3) carbonizing the pre-oxidized product at high temperature and cooling it to obtain a hard carbon material; Among them, the mass ratio of asphalt to ammonium phosphate is 0.5-5, the softening temperature of asphalt is lower than the decomposition temperature of ammonium phosphate, the pre-oxidation heating rate is 1°C / min-5°C / min, the pre-oxidation temperature is 180°C-300°C, the pre-oxidation time is 5h-15h, the high-temperature carbonization is carried out in an inert atmosphere, the high-temperature carbonization heating rate is 10°C / min-20°C / min, the high-temperature carbonization temperature is 1300°C-1700°C, and the high-temperature carbonization time is 2h-4h.

13. A hard carbon material prepared by the preparation method according to any one of claims 1 to 12, characterized in that: The hard carbon material is doped with nitrogen atoms and phosphorus atoms, and contains closed pores.

14. A negative electrode, characterized in that: The negative electrode includes the hard carbon material as claimed in claim 13 as a negative electrode material.

15. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode as claimed in claim 14.

Citation Information

Patent Citations

  • Porous hard carbon negative electrode material based on asphalt as well as preparation method and application of porous hard carbon negative electrode material

    CN115676804A

  • Oxidized asphalt-based hard carbon negative electrode material for sodium-ion battery and preparation method of oxidized asphalt-based hard carbon negative electrode material

    CN115991467A

  • Ammonium phosphate doped modified asphalt-based hard carbon negative electrode material and preparation method thereof

    CN116216693A

  • Preparation method, application and preparation device of low-voltage and high-specific-capacity hard carbon

    CN116443868A